2020
DOI: 10.1088/1361-6528/ab89d0
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-electronics, transport properties, and tuning effects of arsenene armchair nanotubes doped with transition metal atoms

Abstract: Recently, the arsenic monolayer has been successfully fabricated by micromechanical stripping. However, it is a non-magnetic semiconductor, including its derivatives. Here, we theoretically explore how to induce magnetism for arsenene armchair nanotubes (AsANTs) with a low-concentration TM (TM = Co, Y, Rh, Ni, Mo, Ru) atom doping, especially focusing on their structural stability, magneto-electronic property, carrier mobility, and strain effects. The high stability of these doped tubes are confirmed by the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…For the zigzag types, a comparison with other nanotubes indicates that the bandgap is similar to that of BN or GaN nanotubes with an indirect gap, 9,[40][41][42] which is more suitable for transistor applications. The change in the bandgap of silicon-doped arsenic tubes is consistent with that of transition metal atom 43 doped armchair-type arsenic tubes, as well as the change in the bandgap of arsenic tubes under strain. 25 To analyze the effect of doping in armchair-As/SbNTs, the relevant PDOS of s and p orbitals of arsenic, antimony and silicon elements are plotted in Fig.…”
Section: Nanostructuressupporting
confidence: 76%
“…For the zigzag types, a comparison with other nanotubes indicates that the bandgap is similar to that of BN or GaN nanotubes with an indirect gap, 9,[40][41][42] which is more suitable for transistor applications. The change in the bandgap of silicon-doped arsenic tubes is consistent with that of transition metal atom 43 doped armchair-type arsenic tubes, as well as the change in the bandgap of arsenic tubes under strain. 25 To analyze the effect of doping in armchair-As/SbNTs, the relevant PDOS of s and p orbitals of arsenic, antimony and silicon elements are plotted in Fig.…”
Section: Nanostructuressupporting
confidence: 76%
“…As early as 2009, our group designed the Au@TiO 2 /MCM‐41 and Au@TiO 2 /MCM‐22 catalysts, used the characteristics of oxides and molecular sieve at the same time, discovered the ingenuity and excellent catalytic performance of the hybrid nanostructure catalyst. To use the special nanostructure and the synergistic effect, we combine metal nanoparticles, semiconductor metal oxide and support (such as activated carbon (AC) and molecular sieve (SBA‐15)) to develop a novel metal‐2D semiconductor metal oxides hybrid nano‐structure catalyst [64–68] . According to in‐depth research, we found that the challenge of this catalyst was to maintain a stable catalyst structure and improve the atomic utilization of noble metals.…”
Section: The Develop Of Metal‐2d Semiconductor Hybrid Nano‐structure ...mentioning
confidence: 99%
“… Hydrogenation of phenol(a), [68] benzaldehyde(b, c) [68,67] and nitrobenzene and chloronitrobenzene(d) on different catalysts [65] …”
Section: The Structure and Catalytic Performance Of Metal‐2d Semicond...mentioning
confidence: 99%
“…The geometry optimization, examination of structural stability, and calculations of magneto-electronic properties for the As/FGT vdW heterostructure are performed by the first-principles method based on the density functional theory (DFT), as implemented in Atomistix ToolKit [46], which has been widely employed to investigate nano-material properties [47][48][49][50][51]. To solve the Kohn-Sham equation, we choose the Perdew-Burke-Ernzerhof functional in the spin polarized generalized gradient approximation as the exchange correlation potential, and Troullier-Martins norm-conserving pseudopotential are used to represent the atom core.…”
Section: Computational Detailsmentioning
confidence: 99%